Assessment of Awareness, Knowledge, Attitudes, Practices, and Quality of Life Among Glaucoma Patients at a Tertiary Eye Hospital in Nepal - Gautam Adhikari, Pragati; Thapa, Madhu (Tribhuvan University Journal, 2026)
Glaucoma is one of the leading causes of irreversible blindness that affects patients’ quality of life. Adequate awareness, knowledge, positive attitudes, and self-care practices play vital roles in treatment and preservation of visual function in glaucoma patients. This study aimed to assess the levels of awareness, knowledge, attitudes, and practices, and quality of life among diagnosed cases of primary open-angle glaucoma at a tertiary eye care centre in Nepal. A hospital-based cross-sectional study was conducted among 110 patients attending the glaucoma clinic. Data were collected using a structured KAP questionnaire and the Glaucoma Quality of Life-15 (GQOL-15) questionnaire. KAP scores were categorized based on percentage scores, and quality of life was assessed using total GQOL-15 scores. Associations between variables were analyzed using chi-square test, independent t-test, and one-way ANOVA, with a p-value <0.05 considered statistically significant. The mean age of participants was 50.07 ± 15.85 years, and 60% were male. Overall awareness of glaucoma was high (91.8%), with hospitals being the most common source of information (85.5%). The mean knowledge, attitude, and practice scores were 2.74 ± 2.09, 3.51 ± 1.46, and 3.03 ± 1.16, respectively. Only 45.7% of participants demonstrated adequate knowledge regarding glaucoma. Higher educational level and longer disease duration were significantly associated with better knowledge scores (p < 0.05). Good attitude and practice were observed in 63% of participants. Practice score was significantly associated with glaucoma duration (p < 0.001) and attitude (p = 0.002). The mean GQOL-15 score was 17.59 ± 5.62. Poorer quality of life was significantly associated with lower visual acuity (p < 0.001) and female gender (p = 0.02). While awareness was not significantly associated with quality of life (p = 0.30), knowledge, attitude, and practice scores showed significant associations with GQOL-15 score (p < 0.05). In this study, despite high awareness of glaucoma among diagnosed patients, detailed disease knowledge remained limited. Better knowledge, attitudes, and practices were associated with improved quality of life, emphasizing the need for structured patient counselling beyond basic disease awareness.